2017
DOI: 10.1080/2162402x.2017.1316437
|View full text |Cite
|
Sign up to set email alerts
|

Arginase inhibition suppresses lung metastasis in the 4T1 breast cancer model independently of the immunomodulatory and anti-metastatic effects of VEGFR-2 blockade

Abstract: Tumor angiogenesis promotes tumor growth and metastasis. Anti-angiogenic therapy in combination with chemotherapy is used for the treatment of metastatic cancers, including breast cancer but therapeutic benefits are limited. Mobilization and accumulation of myeloid-derived suppressor cells (MDSC) during tumor progression and therapy have been implicated in metastasis formation and resistance to antiangiogenic treatments. Here, we used the 4T1 orthotopic syngenic mouse model of mammary adenocarcinoma to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…Isolated cells can be used for functional experiments or lysed immediately to measure mRNA/DNA content by RNA/DNA sequencing or PCR or detect proteins by proteomics or antibody arrays, during natural tumor progression or in response to treatments, for example to identify pathways and their alteration by drugs [262, 264, 270]. A critical parameter for successful cell isolation is the relative density of the to-be-sorted cells in the starting population: The lower the frequency (e.g., below 1%) the longer the sorting time (which may affect viability) and the lower the purity (which can pose problems for genetic, genomic, or proteomics studies).…”
Section: Flow Cytometry and Cell Sorting Assaysmentioning
confidence: 99%
“…Isolated cells can be used for functional experiments or lysed immediately to measure mRNA/DNA content by RNA/DNA sequencing or PCR or detect proteins by proteomics or antibody arrays, during natural tumor progression or in response to treatments, for example to identify pathways and their alteration by drugs [262, 264, 270]. A critical parameter for successful cell isolation is the relative density of the to-be-sorted cells in the starting population: The lower the frequency (e.g., below 1%) the longer the sorting time (which may affect viability) and the lower the purity (which can pose problems for genetic, genomic, or proteomics studies).…”
Section: Flow Cytometry and Cell Sorting Assaysmentioning
confidence: 99%
“…VEGFA-dependent angiogenesis has been shown to play a role for 4T1 tumor growth and metastasis [ 43 ] although the effects of VEGFR2 inhibition were modest. The vascular plexa shown in Figure 2 are characteristic of VEGFA-dependent angiogenesis [ 44 , 45 ] and their reduction in knockout tumors is in agreement with reduced VEGFA-dependent angiogenesis occurring under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This conforms with what was previously observed in RIP-Tag2 insulinomas [ 32 ], in which VEGFA-dependent angiogenesis was reduced by absence of the Shb gene but compensated for by other mechanisms, such as “inflammation” [ 21 ]. Upon VEGFR2-blocking treatment of 4T1 tumors, an increase in Arg1 gene expression was noted and inhibition of this enzyme reduced metastasis, implicating arginase 1 in metastasis occurring in response to VEGFA inhibition [ 43 ]. The activation of immunosuppressive pre-metastatic niche cells in tumor-bearing conditions results in up-regulated expression of immune suppressive factors such as arginase 1 (encoded by Arg1 ), inducible nitric oxide synthase and Treg cells that inhibit effector T cell function [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining anti-VEGF therapies with check-point inhibitors (e.g., anti-PD-L1) has shown synergy and positive outcomes in phases I to III studies, particularly in patients with high VEGF levels [177] . Using the 4T1 experimental model of TNBC we have demonstrated that inhibition of tumor angiogenesis with the anti-VEGFR-2 antibody DC101, attenuated the inhibitory effect of MDSC on T cell proliferation and decreased the frequency of Tregs in primary tumors and lung metastases [181] . Combined angiopoietin-2 and VEGF inhibition was shown to promote superior vascular regression, tumor necrosis, and enhanced the perivascular recruitment of cytotoxic T lymphocytes, as compared to the single agents in multiple cancer models.…”
Section: Immunological Dormancy: Active Control By the Immune Systemmentioning
confidence: 95%